A roadmap for gene system development in Clostridium. (October 2016) - Minton, Nigel P.; Ehsaan, Muhammad; Humphreys, Christopher M.; Little, Gareth T.; Baker, Jonathan; Henstra, Anne M.; Liew, Fungmin; Kelly, Michelle L.; Sheng, Lili; Schwarz, Katrin; Zhang, Ying
Abstract: Clostridium species are both heroes and villains. Some cause serious human and animal diseases, those present in the gut microbiota generally contribute to health and wellbeing, while others represent useful industrial chassis for the production of chemicals and fuels. To understand, counter or exploit, there is a fundamental requirement for effective systems that may be used for directed or random genome modifications. We have formulated a simple roadmap whereby the necessary gene systems maybe developed and deployed. At its heart is the use of 'pseudo-suicide' vectors and the creation of a pyrE mutant (a uracil auxotroph), initially aided by ClosTron technology, but ultimately made using a special form of allelic exchange termed ACE (Allele-Coupled Exchange). All mutants, regardless of the mutagen employed, are made in this host. This is because through the use of ACE vectors, mutants can be rapidly complemented concomitant with correction of the pyrE allele and restoration of uracil prototrophy. This avoids the phenotypic effects frequently observed with high copy number plasmids and dispenses with the need to add antibiotic to ensure plasmid retention. Once available, the pyrE host may be used to stably insert all manner of application specific modules. Examples include, a sigma factor to allow deployment of a mariner transposon, hydrolases involved in biomass deconstruction and therapeutic genes in cancer delivery vehicles. To date, provided DNA transfer is obtained, we have not encountered any clostridial species where this technology cannot be applied. These include, Clostridium difficile, Clostridium acetobutylicum, Clostridium beijerinckii, Clostridium botulinum, Clostridium perfringens, Clostridium sporogenes, Clostridium pasteurianum, Clostridium ljungdahlii, Clostridium autoethanogenum and even Geobacillus thermoglucosidasius . Highlights: A simple roadmap for the development and deployment of gene systems in clostridia. Allelic exchange using pyrE alleles and pseudo-suicide vectors. Knock-out and knock-in using allele-coupled exchange (ACE). Complementation studies through genome insertion. Genome insertion of application specific modules.